Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.